PEMANFAATAN EKSTRAK KULIT BUAH DELIMA ( PUNICA GRANATUM ) SEBAGAI INHIBITOR KOROSI PADA PIPA BAJA KARBON - Reski Nur Ananda; Cristy Rahayu Manda; Frenly Adhe Pratama; Ahmad Imran; Fitri Oktafiani; Risna Risna (PETROGAS: Journal of Energy and Technology, 2026)
This research examines the potential of pomegranate peel extract (Punica granatum) as an environmentally friendly green corrosion inhibitor to control the rate of corrosion in carbon steel pipes in the petroleum industry. Corrosion in carbon steel causes economic losses and safety hazards, while conventional synthetic inhibitors have a high cost and a bad impact on the environment. Pomegranate peel was chosen because it is an agro industrial waste rich in bioactive compounds such as tannins, flavonoids, polyphenols, and ellagic acid that are able to form a protective layer on the steel surface. The results showed that the administration of extracts with variations of 10 ml, 20 ml, and 30 ml was able to significantly reduce the corrosion rate, with a mass decrease of 23.98 g; 23.52 g; and 23.91 g respectively, much smaller than the inhibitor-free sample. Thus, the pomegranate peel extract shows promising potential as a natural corrosion inhibitor that may help reduce the corrosion rate of carbon steel while offering a more environmentally friendly alternative.